2011
DOI: 10.1007/s00436-011-2633-8
|View full text |Cite
|
Sign up to set email alerts
|

Necrotic enteritis due to simultaneous infection with Isospora suis and clostridia in newborn piglets and its prevention by early treatment with toltrazuril

Abstract: In this study, 51 piglets originating from five different sows were included in the investigations. The animal source of all sows had a history of Clostridium perfringens type A (β2) infection. The piglets of three sows (n = 31) were experimentally infected with Isospora suis within the first 4 h after birth and were randomly assigned to the treatment group or the sham-dosing group. The piglets of the two remaining sows (n = 20) served as I. suis-uninfected controls. Twelve hours post-infection, the animals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
5
42
1
Order By: Relevance
“…In the present study no Eimeria oocysts were detected after early treatment with toltrazuril before or up to 36 h after Eimeria infection, respectively. Similar results were achieved by Mengel et al (2012), who applied a single dose of toltrazuril and completely suppressed oocyst excretion and diarrhoea in piglets co-infected with I. suis and C. perfringens. Mengel et al (2012) also concluded that toltrazuril prevents a severe coccidial multiplication and thus increased mucus production, which would promote a secondary clostridial infection and clinical disease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study no Eimeria oocysts were detected after early treatment with toltrazuril before or up to 36 h after Eimeria infection, respectively. Similar results were achieved by Mengel et al (2012), who applied a single dose of toltrazuril and completely suppressed oocyst excretion and diarrhoea in piglets co-infected with I. suis and C. perfringens. Mengel et al (2012) also concluded that toltrazuril prevents a severe coccidial multiplication and thus increased mucus production, which would promote a secondary clostridial infection and clinical disease.…”
Section: Discussionsupporting
confidence: 81%
“…Arrows, necrotic foci; arrowheads, cell detritus and exudate above destroyed mucosa. laboratory, early treatment with toltrazuril prevented NE resulting from simultaneous infection with Isospora suis and C. perfringens in newborn piglets (Mengel et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…This system provided complete development to oocysts but no sporulation [15]. Beside these findings in vivo infection models for neonatal porcine coccidiosis are well described [16,17] and successfully used for drug efficacy testing [18,19], investigations of the immune response [2022], and for co-infection modeling [23]. Therefore, a reproducible in vitro system including sexual stages and sporulated oocysts together with the knowledge obtained during in vivo trials could deliver an integral approach to the understanding of neonatal porcine coccidiosis and coccidian development as well as host-parasite interactions in these parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data obtained in this study, E. zuernii is likely to play a crucial role in massive multiplication of C. perfringens under certain conditions, such as stress in response to transportation or vitamin A deficiency, which underpins the pathophysiology demonstrated in pigs (Mengel and others 2012) and chickens (Collier and others 2008). Both E. zuernii and clostridia are widely distributed in cattle farms, and thus, severe E. zuernii infection and subsequent overgrowth of C. perfringen s in the intestine appear to be a likely event in conventional herds.…”
Section: Discussionmentioning
confidence: 80%